Financing of state-owned entities: Can the Trade-off Theory explain the debt structure? - Sharanam Abbana; Ferina Marimuthu (Research Synergy Foundation, 2023)
The purpose of this research is to determine if the financing behaviour of South African state-owned entities (SOEs) have a target capital structure which they adjust towards and if so, the speed of adjustment, a central tenet of the Trade-off Theory. An unbalanced panel data set from a sample of thirty-three commercial SOEs were studied using a dynamic partial adjustment model. The findings provide strong evidence that South African SOEs follow the trade-off theory based on the existence of a target capital structure and speed of adjustment of 21.5% per annum towards the target which is slower than other SOEs in developing economies. The findings also revealed that these SOEs take almost five years to close off two-thirds of the gap between the actual and optimal capital structures. The findings will be of interest to observers of the economy, as they measure the capacity of SOEs to play a leading role in investment and in improving the efficiency of the economy. They could also inform decision making and policy development on SOEs.